Biomechanical strategies to maximize gait attractiveness among women - Tanabe, Hiroko; Fujii, Keisuke; Kaneko, Naotsugu; Yokoyama, Hikaru; Nakazawa, Kimitaka (Frontiers in Sports and Active Living, 2023)
Physical attractiveness is a key factor in social communication, and through this communication process, we attractively brand and express ourselves. Thus, this study investigated the biomechanical strategies used by women to express gait attractiveness. Our aim was to extend the current literature by examining this aspect of dynamic motion from the perspective of expressed, rather than perceived attractiveness. In this regard, we obtained motion capture data from 17 women, including seven professional fashion models. The participants walked on a treadmill under two conditions: 1) a normal condition in which they were instructed to walk as casually as possible; and 2) an attractive-conscious condition where they were asked to walk as attractively as possible. Then, we used whole-body kinematic data to represent motion energy at each joint, flexibility of the upper body, and the up-down/forward-backward silhouettes of the limbs, and compared these parameters between the two conditions by using statistical parametric mapping. During the attractive-conscious condition, the non-model women increased the energy of the hip and thoracolumbar joints, which emphasized the motions of their bosoms and buttocks. They also increased their upper body flexibility (possibly reflecting fertility) and continued to face front and downward. Conversely, although the fashion models partially shared the same strategy with the non-models (e.g., hip energy, upper body flexibility, and head bending downward), the strategy of the former was prominent in the stretching of the knee during the push-off phase and pulling the upper arm back, allowing them to showcase their youth and emphasize their chests. In addition, the fashion models used a wider variety of strategies to express their gait attractiveness. The findings indicate that the biomechanical strategy used to express gait attractiveness in women involves showcasing femininity, fertility, and youth. Our results not only deepen the understanding of human movement for self-expression through gait attractiveness, but they also help us comprehend self-branding behavior in human social life.